When stripes in clothes deceive: Cross-cultural examination of perceptual and belief discrepancies about horizontal stripes in clothes - Antonis Koutsoumpis; Elias Economou; Zai-Fu Yao; Erik Van der Burg (PLoS ONE, 2026)
Despite the common belief that horizontal stripes in clothes make someone look wider, behavioral studies show that horizontally striped stimuli are perceived as thinner compared to equally wide non-striped stimuli. In the present study, we examined the extent to which participants’ beliefs regarding the thinning or widening effect of horizontal stripes were related to their visual perception of horizontally striped versus neutral stimuli in a behavioral task. Data were collected across three countries to explore possible cross-cultural generalizability of the phenomenon. In Experiment 1 ( n = 316; Greece, Netherlands), we measured participants’ beliefs regarding the effect of horizontal stripes in clothes, verifying the popular belief that horizontal stripes are, indeed, thought to have a widening effect regardless of country. In Experiment 2 ( n = 419; Greece, Netherlands, Taiwan), participants self-reported their beliefs regarding the effect of horizontal stripes and, also, completed a behavioral task comparing the width of a striped and non-striped dress. The results showed that (a) in line with previous research, the horizontally striped dress was perceived as thinner compared to the non-striped dress, and (b) the more participants believed that horizontal stripes make someone look thin, the more they perceived the striped dress as thinner. However, the relation between beliefs and size perception was non-significant for participants who believed that horizontal stripes make someone look wider. No cross-cultural differences were found for this asymmetrical effect, highlighting the universality of the findings.